Cognitive complaint in early Parkinson's disease: A pilot study. (22nd August 2017) - Dupouy, J.; Ory‐Magne, F.; Mekies, C.; Rousseau, V.; Puel, M.; Rerat, K.; Pariente, J.; Brefel‐Courbon, C.; ,
Abstract : Background: Subjective cognitive complaint (SCC) is a criterion recommended by the Movement Disorder Society (MDS) task force for the diagnosis of mild cognitive impairment (MCI). Until now there were few specific tools for detecting SCC in PD. We sought to develop a new tool to assess SCC specifically dedicated for PD. Materials and Methods: We set a group of experts in movements disorders and neurocognition to develop an easy‐to‐use tool based on a visual analogue scale (VAS) for five cognitive domains: memory, executive functions, spatial orientation, attention, and language. We use it to assess SCC twice (at a one‐month interval) in PD patients with disease duration of less than 5 years. Comprehensibility of the VAS was assessed. Controls were assessed with the same VAS. Patients with PD also underwent neuropsychological testing. Results: VAS was easily understandable by the 70 patients with PD. We found significant SCC for the patients with PD vs controls in three cognitive domains: executive functions (1.7 ± 1.9 vs 0.8 ± 1.1; P < .001), language (2.3 ± 2.5 vs 1.0 ± 1.3, P < .001), and attention (2.1 ± 2.2 vs 1.2 ± 1.2; P < .01). Reproducibility between the two evaluations of patients with PD was good. There was no relationship between SCC and the results of neuropsychological testing. Conclusions: SCC seems to appear early in PD, in three cognitive domains (executive functions, language, and attention), and VAS might be a good way to detect SCC in PD, but need to be validated.